FAMILY SUPPORT TO ADOLESCENTS WITH THALASSEMIA (Jurnal Mitra Kesehatan, 2021)
Introduction: Thalassemia is one of the genetic disorders characterized by the decrease or absence of one of the globin chains, either alpha chain or beta chain. Which are the main components of normal hemoglobin. Thalassemia has become serious health issue in Mediterranean, Middle East, India, and South East Asia, including Indonesia. The thalassemia gene frequency in Indonesian population ranging from 3-8%. Adolescent is the transition period from children to adult. Thalassemia adolescents express psychosocial reaction and unpleasant experience due to the lifetime treatment routines that they must face off. These impact on the adolescents’ family and self-esteem. This study aims to analyze the relationship between family support and self-esteem of thalassemia adolescents. Method: This was a quantitative study design with phenomenology approach. A total of 50 subjects were collected with purposive sampling technique. Data were obtained by from questionnaire and analyzed using Spearman Rho method with cross sectional approach. Results: The statistical result with Spearman Rho method shows significant p value of 0.024 (p <0.05) and r value of 0.319. The positive correlation implies that both variables are moving in same direction with weak relationship. These results are in accordance with the hypothesis that family support are related with self-esteem of thalassemia adolescents. Conclusion: Family support in thalassemia adolescents is high and no thalassemia adolescents present with low self-esteem, mostly normal. The correlation between these two variables is weak but significant.